Penguatan budaya hukum masyarakat untuk menghasilkan kewarganegaraan transformatif - Purba, Iman Pasu (Jurnal Civics: Media Kajian Kewarganegaraan, 2017)
Transformative citizenship becomes a crucial discourse to be realized both in civil and political life in order to achieve national state. Establishing transformative citizenship means shaping critical and active citizen on emergent issues as well as aware their role and function in political life. One of important things is their involvement in law system. According to Lawrence Friedman the element of system of law consists of structure of law, material of law and culture of law. Cultural law is the rarest element focused seriously by stakeholders in developing law. In diversity context of religion, race, local culture such as those in Indonesia, it is a challenging effort to develop national law. Therefore, it is important to enforce cultural law in order achieve the purpose of law.